Reconstructing extraction techniques at Stonehenge's bluestone megalith quarries in the Preseli hills of west Wales. (December 2022) - Parker Pearson, Mike; Bevins, Richard; Pearce, Nick; Ixer, Rob; Pollard, Josh; Richards, Colin; Welham, Kate
Highlights: Stone wedges were among the most common tools at Stonehenge's bluestone megalith quarries in Wales. Three stone wedges were found in situ at the bluestone quarry of Craig Rhos-y-felin. Two of these wedges with evidence of being driven into joints around a pillar. Geochemical analysis confirmed that these two wedges had been introduced into these joints from elsewhere. Abstract: Excavations at two of the sources of Stonehenge's bluestones in Mynydd Preseli, west Wales, have led to the discovery of stone tools associated with megalith quarrying in the final centuries of the fourth millennium BC, shortly before the suspected date of the bluestones' erection at Stonehenge, 240 km away. Among the most plentiful of these tools are stone wedges, three of which were found in situ at the rhyolite bluestone quarry of Craig Rhos-y-felin. Two of these were positioned in the joints of a rhyolite pillar adjacent to a recess left by a removed pillar. Geochemical analysis reveals that these and the third wedge are of compositions different to the rock on either side of the cracks into which they had been driven, confirming their identification as quarrying tools. This research sheds new light on the methods used to extract the stones for Stonehenge.